TANTANGAN DI ERA MILENIAL DALAM MENANGKAL BUDAYA ASING DENGAN MENGEDEPANKAN SIKAP NASIONALISME - Komariah Komariah (Pusat Kajian Islam dan Kemasyarakatan (PKIK), UIN Sultan Maulana Hasanuddin Banten, 2020)
As we know, cultural values ​​that characterize the Indonesian nation, such as mutual cooperation, friendship, and hospitality in society, are basic features that can make individuals in Indonesian society to love and preserve their own national culture. However, the characteristics of Indonesian society which are known as friendly and polite people are now starting to fade since the entry of foreign cultures into Indonesia that cannot be properly selected by Indonesians. In this case, the government has an important role in maintaining the values ​​of Indonesian culture in the life of its people because the cultural values ​​of the ancestors are the philosophy of life in each region even without the help of technology. These cultural values ​​do not mean that we must be closed to foreign cultures, but the values ​​and philosophical meanings of Indonesian culture must be used as a source of inspiration and creativity. The following are some ways to maintain Indonesian culture so as not to be influenced by negative foreign cultures, 1) Fostering a strong spirit of nationalism 2) Instilling and practicing the values ​​of Pancasila as well as possible 3) Inculcating and implementing religious teachings as well as possible 4 ) Be selective about foreign cultures that enter Indonesia 5) Strengthen and maintain the national identity so that it does not fade. That way people can act wisely in determining their attitude so that the nation's identity and personality does not fade because of the foreign culture that has entered Indonesia